The Meta-Evaluation of the Sports Participation Impact and Legacy of the London 2012 Games: Methodological Implications. Issue 1 (2nd April 2016) - Henry, Ian
ABSTRACT: The London 2012 Games were subject to the most substantial evaluation of any of the Olympic Games, or indeed any other sporting event, to date, in the form of a meta-evaluation. Meta-evaluations evaluate the collective lessons learned from smaller individual evaluation studies and consist of two principal elements. The first reports a synthesis of the results of the evaluations of individual programmes and projects, and of national participation data; and the second consists of an evaluation of the rigour of the methods adopted in project and programme evaluation and national evaluation studies, and of the conclusions drawn. The paper addresses one of the high-profile legacy goals associated with the 2012 Games, increased sports participation, and seeks to explain the disjunction between national-level participation data indicating little or no increase in participation and programme or project data suggesting significant increases, and thus highlights the limits to this specific application of the meta-evaluation approach.